The Anatomy of Behavioral Responses to Social Assistance when Informal Employment is High - Bérgolo Sosa, Marcelo (2016)
The disincentive effects of social assistance programs on registered (or formal) employment are a first order policy concern in developing and middle income countries. Means tests determine eligibility with respect to some income threshold, and governments can only verify earnings from registered employment. The loss of benefit at some level of formal earnings is an implicit tax – a notch – that results in a strong disincentive for formal employment, and there is extensive evidence on its effects. We study an income-tested program in Uruguay and extend this literature by developing an anatomy of the behavioral responses to this program and by establishing its welfare implications in full. Our identification strategy is based on a sharp discontinuity in the program’s eligibility rule. We rely on information on the universe of applicants to the program for the period 2004-2012 (about 400,000 individuals) from the program’s records, from administrative data on registered employment from the social security administration, and from a complementary follow-up survey with information on informal work. We construct the anatomy of the program’s effects along four dimensions. First, we establish that, as predicted by the theory, beneficiaries respond to the program’s incentives by reducing their levels of registered employment by about 8 percentage points. Second, we find substantial heterogeneity in these effects: the program induces a larger reduction of formal employment for individuals with a medium probability to be a registered employee, suggesting some form of segmentation – those with a low propensity to work formally do not respond to the financial incentives of the program, probably because they have limited opportunities in the labor market to begin with. Third, the follow-up survey allows us to establish that the fall in registered employment is due to a larger extent (about two thirds) to an increase in unregistered employment, and to a lesser extent (about one third) to a shift towards non-employment. Fourth, we find an elasticity of participation in registered employment of about 1.7. These results imply a deadweight loss from the behavioral responses to the program of about 3.2% of total registered labor income